DINAMIKA PENAFSIRAN PRINSIP KEPENTINGAN TERBAIK DALAM PERKARA HAḌONAH DAN RIDDAHNYA PIHAK PENGASUH - Ali Akbar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to obtain different results, judges in the Religious Courts view riddah in resolving post-divorce conflict cases and information with the determination of Islamic law. The approach used is empirical juridical which aims to examine practice in the form of decisions by referring to legal norms and the basis for legal considerations regulated in regulations. The data sources of this research use several decisions of the Religious Courts, laws and regulations, especially laws and primary legal materials. The results of the study show that the understanding of parenting is contained in the terms in Fiqh and in the Laws, which emphasize the welfare of the child with the caregiver being able to fulfil all the rights of the child. from the cases that have been explained that the judge has a subjective view in making decisions which ultimately fulfil the rights of the child.